Perlindungan Hukum Hak-Hak Narapidana Anak di Lembaga - Komang Angga Pradana; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Warmadewa Press, 2021)
Acts against the law against children are now increasing in the country, children are one of the creations of God Almighty as his creation with the age of children under 18 years old or unmarried are still unstable towards behavior, their emotions are still unstable should be more receive full attention in correctional institutions. This study aims to analyze the regulation of the child education system in special coaching institutions and legal protection for child prisoners in special coaching institutions. This type of research uses the normative method, using the Legislative and Conceptual approach. The sources of legal materials used are primary and secondary legal sources. The technique of collecting data on legal materials used is through recording, namely by quoting. The analysis of legal materials used in this research is descriptive-qualitative. The results of the study reveal that the justice and education system is regulated in the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System while the legal protection of children is regulated in the Law of the Republic of Indonesia Number 35 of 2014 amendments to Law Number 23 of 2002 concerning Child protection. Correctional officers should better understand and adapt to the conditions and situations of Indonesia without ignoring the methods or procedures for protection carried out by other countries that should be considered and imitated.